Mycofloral profile and the radiation sensitivity (D(10) values) of solar dried and gamma irradiated Pleurotus ostreatus (Jacq.Ex. Fr.) Kummer fruitbodies stored in two different packaging materials - Kortei, Nii Korley (Food Sci Nutr, 2017)
The presence of fungi in our foods poses serious health risks as some genera of fungi may produce certain mycotoxins which have carcinogenic, mutagenic, teratogenic, and immunosuppressive effect on humans and animals alike. Fruitbodies of Pleurotus ostreatus were solar dried at a moisture content of 12.5 ± 0.2% and stored in polythene and polypropylene packs, gamma irradiated at doses of 0 (control), 1, 2, 3, 4, and 5 kGy at a dose rate of 1.7 kGy/hr from a Cobalt 60 source (SLL, 515, Hungary) and stored at room temperature 28–30°C for a period of 12 months. Mycological analyses were done at intervals of 0, 3, 6, and 12 months. A total of eleven (11) fungi belonging to eight fungal genera were isolated on both Cooke's and DRBC media; Aspergillus (A. niger, A. flavus, A. fumigatus, A. tamarii), Rhizopus (R. oligosporus), Mucor (M. racemosus), Fusarium (F. oxysporum), Penicillium (Penicillium sp.), Trichoderma (T. viride), and Rhodotorula sp. were recorded. There was a significant (p < .05) reduction in initial mycofloral population by an average of 2.2 log cycles as well as in species numbers with increasing doses of radiation. Radiation sensitivity (D(10) values) also ranged between 1.68–2.78 kGy. Gamma irradiation treatment is one way which can enhance food safety through the reduction in potential pathogens and has been recommended as part of a comprehensive program to enhance food safety.